QUALITY OF LIFE AND SOCIAL SUPPORT OF CHILDREN WHO SUFFERED DUE TO MILITARY ACTIONS (Physical Culture and Sport: Scientific Perspective, 2025)
The article investigates the quality of life and the level of social support of children who suffered as a result of military actions. The aim of the study is to assess the level of quality of life and social support for children affected by military actions, particularly to determine the impact of military conflicts on their physical and mental health, as well as to analyze the role of social support from family and friends in their psychological recovery. The research methods used to explore the topic include theoretical methods, empirical methods (sociological studies, SF-36, MSPSS), and mathematical statistics. The study involved 197 children, aged 8 to 12 years, who were affected by military actions, consisting of 92 girls and 105 boys. The results showed that children who had not directly experienced the impact of war maintained high quality of life scores, although in some cases, mental health was found to be diminished (scores for social functioning and mental health were 73.5±6.8 and 71.2±7.4). For children who had experienced the consequences of war, the quality of life scores on the SF-36 scale were significantly lower. Physical functioning remained at an acceptable level (71.7±7.1), but in some cases, it dropped to 63.4±6.5, indicating physical impairments. The assessment of general health (GH) was reduced (63.8±6.1), reflecting both objective disruptions and subjective perceptions of health. The vitality (62.1±5.9 – 58.3±6.7) and social functioning (68.4±6.3 – 61.7±6.9) scores also decreased, indicating rapid fatigue and difficulties in social interactions. The mental health of the children who suffered from the war was significantly lowered (67.2±6.8 – 60.5±7.1), indicating anxiety and emotional exhaustion. The study also examined the level of social support for children who had experienced the war. According to the MSPSS scale, children received the most support from their family and friends, particularly in the emotional aspect. Correlation analyses showed strong positive correlations between the level of social support and overall quality of life (the highest correlation was between support from significant others and friends, r = 0.50**). Factor analysis revealed three main factors of social support, explaining 73.59% of the variability of the data. Overall, the results of the study confirm the importance of social support for children who have experienced the consequences of war and its role in improving their psychological and physical health.
Keywords: social-pedagogical rehabilitation; psychological rehabilitation; children; quality of life; post-war society